Comparison of Learning Software Architecture by Developing Social Applications versus Games on the Android Platform. (10th September 2012) - Wu, Bian; Wang, Alf Inge
Abstract : This paper describes an empirical study where the focus was on discovering differences and similarities in students working on development of social applications versus students working on development of games using the same Android development platform. In 2010-2011, students attending the software architecture course at the Norwegian University of Science and Technology (NTNU) could choose between four types of projects. Independently of the chosen type of project, all students had to go through the same phases, produce the same documents based on the same templates, and follow exactly the same process. This study focuses on one of projects—Android project, to see how much the application domain affects the course project independently of the chosen technology. Our results revealed some positive effects for the students doing game development compared to social application development to learn software architecture, like motivated to work with games, a better focus on quality attributes such as modifiability and testability during the development, production of software architectures of higher complexity, and more productive coding working for the project. However, we did not find significant differences in awarded grade between students choosing the two different domains.